Do domestic budgerigars perceive predation risk? - Chang Wang; Xueqi Zhao; Baodan Tao; Jiaqi Peng; Haitao Wang; Jiangping Yu; Longru Jin (Animal Cognition)
Abstract Predation risk may affect the foraging behavior of birds. However, there has been little research on the ability of domestic birds to perceive predation risk and thus adjust their feeding behavior. In this study, we tested whether domestic budgerigars (Melopsittacus undulatus) perceived predation risk after the presentation of specimens and sounds of sparrowhawks (Accipiter nisus), domestic cats (Felis catus), and humans, and whether this in turn influenced their feeding behavior. When exposed to visual or acoustic stimuli, budgerigars showed significantly longer latency to feed under sparrowhawk, domestic cat, and human treatments than with controls. Budgerigars responded more strongly to acoustic stimuli than visual stimuli, and they showed the longest latency to feed and the least number of feeding times in response to sparrowhawk calls. Moreover, budgerigars showed shorter latency to feed and greater numbers of feeding times in response to human voices than to sparrowhawk or domestic cat calls. Our results suggest that domestic budgerigars may identify predation risk through visual or acoustic signals and adjust their feeding behavior accordingly.